Anthropologie - Sapir, Edward (Bibliothèque idéale des sciences sociales, 2021)
Edward Sapir is undoubtedly one of the most important anthropologists of the early 20th century. Long before the development of structural anthropology, Sapir formulated the philosophy of structuralism and laid the foundations of a general science of behaviour. Because the individual and society, culture and personality are inseparable, Sapir founded a method at the crossroads of ethnology and linguistics which, combining the concepts and methods of ethnology and psychoanalysis, appears today as a prophetic programme of the tasks incumbent on anthropology. This specialist in Amerindian languages and cultures did not write any comprehensive work during his lifetime, with the exception of a volume on language and a series of monographs on North American Indian languages and cultures. His work is scattered in numerous articles published between 1917 and 1938 some of which were compiled by David Mandelbaum in 1949 under the title Selected Writings of Edward Sapir in Language, Culture and Personality. A selection was also translated into French by Christian Baudelot and Pierre Clinquart, published in two volumes by Éditions de Minuit in 1967. The volume we are offering today, exclusively in digital format, is the re-edition of this French selection presented in the Minuit edition by Christian Baudelot. Our edition offers a translation which has been entirely reread, corrected and annotated by Pierre Clinquart, and augmented by an unpublished preface by the anthropologist Francis Zimmermann.